Perbandingan Konsep Kesaktian Menurut Agama Buddha Dengan Pandangan Kejawen - Catari Paramita; Lauw Acep; Jo Priastana (Dhammavicaya : Jurnal Pengkajian Dhamma, 2020)
Scientific discussion about magic will help people to access information about magic powers. Research on the comparison of the concept of magic in the view of Buddhism and Kejawen's view is an interesting discussion and contributes to the treasures of science. This thesis research aims to examine the concept of magic in the view of Buddhism and the concept of magic in the view of Kejawen. In-depth study will provide a clear picture of each concept. Supernatural powers complement the history of human development inherent in cultural traditions. Power is a high inner and body ability, used to help survival. In the history of Buddhism and Kejawen, magic is inherent in the religious system which is believed to have a great influence on life.